Indigenous Perspectives on the Co-management of a Regional Conservation Area in the Peruvian Amazon - Natalia Arcos Cano; Michael P. Gilmore; Elizabeth Benson; Diego Valderrama; David Dimitrie; Brian M. Griffiths (Environmental Management, 2026)
Growing awareness of the critical role Indigenous Peoples and Local Communities (IPLCs) play in biodiversity conservation has underscored the need to shift conservation practices towards empowering IPLCs, supporting their land rights, traditional practices, and facilitating their political involvement. Despite IPLCs governing over 32% of global land, historically these communities have faced systemic marginalization and violence in the name of conservation. In response, international calls to action and policies have aimed to enhance IPLC participation in environmental governance through mechanisms like co-management. Adaptive Co-management (ACM) emerges as a promising approach, combining adaptive management’s flexibility with co-management’s collaborative principles. This study evaluates the ACM framework within the Maijuna-Kichwa Regional Conservation Area (MKRCA) in the Peruvian Amazon, established to protect the ancestral lands and biocultural resources of the Maijuna and Kichwa communities. Using a Community-Based Participatory Research (CBPR)-informed approach, we conducted interviews with 36 community members to assess their perspectives on the MKRCA’s co-management. Findings reveal significant improvements in resource abundance and community safety but also highlight issues with governmental support, communication, and equitable participation. Highly engaged participants voiced the strongest criticisms, underscoring how participation level shaped perceptions of governance. Recommendations were derived from participant perspectives but synthesized by the authors rather than fully co-developed. The study emphasizes the need for continuous evaluation and enhanced stakeholder engagement to optimize ACM’s effectiveness, offering culturally responsive recommendations to strengthen the MKRCA’s management and achieve its conservation objectives.

Correction: Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2026)

Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2025)
The conservation of biocultural diversity in the Amazon rainforest has become an international priority in the face of global change. Megadevelopment projects threaten conservation efforts and the rights of Indigenous communities to manage their ancestral lands. We examine the potential impacts of one proposed highway development project in the Peruvian Amazon, the Bellavista-El Estrecho Highway, on local and Indigenous communities and natural protected areas in the region. We found that zones of influence of the proposed highway eclipse 343 Indigenous communities of at least 33 000 Indigenous people of ten distinct cultures, 43 503 km 2 of community land, and 26 210 km 2 of natural protected areas including the entirety of the Maijuna–Kichwa Regional Conservation Area and the unique high terrace ecosystems it holds. Under international and national law in Peru, Indigenous communities who will be affected by megadevelopment projects like this highway must be engaged in prior consultation.

Female treefrog preference for breeding sites matches offspring performance in the presence of two anuran competitors - David A. Dimitrie; Michael F. Benard (Ecology, 2023)
Preference‐performance theory predicts that females should select breeding sites that maximize offspring performance. Amphibians have been a model system for investigating habitat selection, yet most studies have focused on habitat selection in response to predators and conspecifics. We investigated female oviposition site selection and larval performance in eastern gray treefrogs ( Hyla versicolor ) among pools with and without one of two ecologically distinct heterospecific larvae, the green frog ( Rana clamitans ) and the American bullfrog ( Rana catesbeiana ). Pools without heterospecifics were used on more nights and had more eggs deposited compared to pools with heterospecifics. In a competition experiment, treefrog larval performance matched this female preference: tadpoles developed faster and grew larger in the absence of either heterospecific. Although we hypothesized that bullfrogs would more strongly affect female treefrog preference and offspring performance because of previous work demonstrating that bullfrogs had stronger negative effects on other tadpoles, both heterospecifics elicited similar responses. The effects of heterospecifics on anuran breeding site selection are understudied and not well understood, and our results demonstrate that female selection of breeding sites is an adaptive behavior for offspring in the presence of heterospecific competitors.

Joint Toxicity of Chlorpyrifos and Endosulfan to Pacific Treefrog (Pseudacris regilla) Tadpoles - David A. Dimitrie; Donald W. Sparling (Archives of Environmental Contamination and Toxicology, 2014)